Community Participation as a Form of Power Distribution in the Management of Bukit Tuamese Tourism Objects - Usboko, Ignasius; Suni, Melkianus; Sengkoen, Mariano (Universitas Tanjungpura, 2024)
Tuamese Hill is a tourism object in Tuamese Village, Biboki Anleu District, North Central Timor Regency, NTT. This study aims to analyze the participation of the Tuamese Village community in managing the tourism object, using the Participatory Typology Framework proposed by Arnstein (1969). This qualitative descriptive research with a case study approach was conducted in May-August 2022. The results showed that community participation in the management of the Tuamese Hill was at the top level, which represented the ideal form of community participation, namely Citizen Power, with the type of Delegated Power and Citizen Controls. Meanwhile, the most important inhibiting factor for community participation in the management of Bukit Tuamese is the absence of formal legal rules at the village level to ensure inclusive community participation. This condition is exacerbated by the lack of awareness about the importance of these formal legal rules, especially to provide a basis for authority and opportunities for managing and utilizing the results of inclusive tourism objects, and for obtaining contributions from tourism objects for Village Original Income (PAD).